2018
DOI: 10.1242/jcs.214411
|View full text |Cite
|
Sign up to set email alerts
|

H2AFX and MDC1 promote maintenance of genomic integrity in male germ cells

Abstract: In somatic cells, and are close functional partners in DNA repair and damage response. However, it is not known whether they are also involved in the maintenance of genome integrity in meiosis. By analyzing chromosome dynamics in spermatocytes, we found that the synapsis of autosomes and X-Y chromosomes was impaired in a fraction of cells. Such defects correlated with an abnormal recombination profile. Conversely, was dispensable for the synapsis of the autosomes and played only a minor role in X-Y synapsis, c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 75 publications
0
34
1
Order By: Relevance
“…Histone 2A family members (H2AFs) are one of the components of nucleosomes and are crucial for gene regulation in the host [14]. Physiologically, H2AFX has been shown to promote the maintenance of genome integrity in male germ cells [15]. In breast cancer, copy number alterations and promoter genetic variations appear to correlate with breast carcinogenesis and the risk of sporadic breast cancer [16].…”
Section: Introductionmentioning
confidence: 99%
“…Histone 2A family members (H2AFs) are one of the components of nucleosomes and are crucial for gene regulation in the host [14]. Physiologically, H2AFX has been shown to promote the maintenance of genome integrity in male germ cells [15]. In breast cancer, copy number alterations and promoter genetic variations appear to correlate with breast carcinogenesis and the risk of sporadic breast cancer [16].…”
Section: Introductionmentioning
confidence: 99%
“…H2afx, also known as H2ax, is a variant of histone H2a and represents 2%-25% of total H2a (Rogakou et al 1998). The phosphorylated form of H2AFX (γ-H2AFX) plays a critical role in DNA repair and maintenance of genomic integrity (Rogakou et al 1998;Bassing et al 2002;Celeste et al 2002Celeste et al , 2003aYuan et al 2010;Testa et al 2018). In addition, H2afx is also required for the chromatin remodeling of sex chromosomes and meiotic silencing in mouse (Fernandez-Capetillo et al 2003;Cloutier et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Our data presented here demonstrate age-related upregulation of pathways associated with DNA replication and repair, double strand break repair, and response to DNA damage, all of which may underlie the well-characterized differences between spermatocytes in the first wave compared to steady-state spermatocytes. Included in these sets of variably-expressed genes are known regulators of DNA damage response and cross-over formation including Rad51 33 , Brip1 29 , and H2afx 34 , as well as Brca1 and Brca2 3032 and Atm 35,59 , all of which increase in spermatocytes with age, effects which we have also shown at the protein level for both RAD51 and ATM ( Figures 10, S11, S12 ). While the cause of this lower expression in the first wave is unknown, it has been demonstrated that spermatocytes from juvenile mice generate only about 25% of the double strand breaks present in spermatocytes from steady-state spermatogenesis 59 .…”
Section: Discussionmentioning
confidence: 60%
“…From this analysis, we observe decreasing expression of genes related to translation and post-transcriptional regulation, and increasing expression of genes related to DNA replication, double strand break repair, and cell cycle regulation ( Figure 7 & S6B, Table S6 ). Most notable in the list of genes upregulated in spermatocytes of increasing age are those known to be essential to DNA repair, meiotic progression, and crossover formation including Brip1 29 , Brca1 and Brca2 3032 , Rad51 33 , H2afx 34 and Atm 35 . Many of these pathways, particularly those related to double strand break repair (which initiates meiotic recombination), may be crucial for understanding the molecular mechanisms underlying fundamental differences in first-wave spermatocytes.…”
Section: Resultsmentioning
confidence: 99%